2019
DOI: 10.1186/s12877-019-1377-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke patients with moderate function have the greatest risk of falls: a National Cohort Study

Abstract: BackgroundStroke patients have increased risks of falls. We examined national registry data to evaluate the association between post-stroke functional level and the risk of low falls among post-stroke patients.MethodsThis retrospective cohort study analyzed data from national registries to examine the risk factors for post-stroke falls. Data for patients who suffered ischemic strokes and survived the index hospital admission was obtained from the Singapore National Stroke Registry and matched to the National T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Balance is an essential component of the quality of walking (2)(3)(4), and in stroke survivors, balance impairment may determine abnormal patterns of gait characterized by decreased walking speed and stride length and spatial and temporal asymmetry (5)(6)(7)(8)(9) that in turn increase the risk of falling (10)(11)(12)(13)(14). Because balance and gait disorders may persist also in the chronic stage (15), they represent one of the main limiting factors for individual independence and participation in social activities, reducing patients' quality of life (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Balance is an essential component of the quality of walking (2)(3)(4), and in stroke survivors, balance impairment may determine abnormal patterns of gait characterized by decreased walking speed and stride length and spatial and temporal asymmetry (5)(6)(7)(8)(9) that in turn increase the risk of falling (10)(11)(12)(13)(14). Because balance and gait disorders may persist also in the chronic stage (15), they represent one of the main limiting factors for individual independence and participation in social activities, reducing patients' quality of life (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have also found a relationship between functionality and either the risk of falling and/or the occurrence of falls, regardless of the scale used to assess functionality. 33,[36][37][38][39] The current study highlights that the estimation of the risk for falls based on the usual tools has low discrimination ability in these Portuguese community-dwelling stroke survivors with autonomous gait. However, it is important to note that in this research only factors related to mobility and balance were considered and risk factors for falls may be related to other key areas.…”
Section: Discussionmentioning
confidence: 77%
“…From an inversed U-shaped relationship found between fall and MRS, those with MRS ≥2 were more likely to fall than those with lower or higher functional status. This scenario can be due to the low physical activity in the lower functional status group and intact motor-sensory function in the higher functional status group [ 10 ]. Therefore, stroke survivors with underlying osteoporosis were more likely to have MRS 2 or more (poor function) and at increased risk of fall, leading to injuries and fractures.…”
Section: Introductionmentioning
confidence: 99%